The Influence of Heat Treatment and Laser Alternative Surface Treatment Methods of Non-Alloy Steels: Review - Oleksandr Kapustynskyi; Nikolaj Višniakov (Photonics)
This paper focuses on the microstructural characteristics of non-alloy structural steels with carbon contents below 0.3% (further—Low-Carbon Steel—LCS), as well as the possible structural transformations and the resultant mechanical properties attainable through conventional heat treatment or alternative surface treatment methods. The principal microstructural constituents that govern the properties of these steels include both equilibrium and non-equilibrium phases, such as martensite, retained austenite, sorbite, and troostite. Conventional methodologies for enhancing rigidity involve the implementation of supplementary stiffening ribs, which augment rigidity while concomitantly contributing to an increase in overall weight or dimensions of the structure. In structures where supplementary stiffening ribs are incorporated within the thin-walled steel shell, this may reduce manufacturing efficiency and simplicity of design. Modern laser treatment technologies for thin-walled steel structures, however, involve modifying the internal microstructure and creating rigidity ribs within the structure itself, thus circumventing the need for additional elements.